Plant Species Identification Using Multi-scale Fractal Dimension Applied to Images of Adaxial Surface Epidermis - Backes, Andre R. (2009)
This paper presents the study of computational methods applied to histological texture analysis in order to identify plant species, a very difficult task due to the great similarity among sortie species and presence of irregularities in a given species. Experiments were performed considering 300 x 300 texture windows extracted from adaxial surface epidermis from eight species. Different texture methods were evaluated rising Linear Discriminant Analysis (LDA). Results showed that methods based on complexity analysis perform a better texture discrimination; so conducting to a, more accurate identification of plant species.